Targeting gp100 and TRP-2 with a DNA vaccine: Incorporating T cell epitopes with a human IgG1 antibody induces potent T cell responses that are associated with favourable clinical outcome in a phase I/II trial. (3rd June 2018) - Patel, Poulam M.; Ottensmeier, Christian H.; Mulatero, Clive; Lorigan, Paul; Plummer, Ruth; Pandha, Hardev; Elsheikh, Somaia; Hadjimichael, Efthymios; Villasanti, Naty; Adams, Sally E.; Cunnell, Michelle; Metheringham, Rachael L.; et al.
ABSTRACT: A DNA vaccine, SCIB1, incorporating two CD8 and two CD4 epitopes from TRP-2/gp100 was evaluated in patients with metastatic melanoma. Each patient received SCIB1 via intramuscular injection with electroporation. The trial was designed to find the safest dose of SCIB1 which induced immune/clinical responses in patients with or without tumour. Fifteen patients with tumor received SCIB1 doses of 0.4-8 mg whilst 20 fully-resected patients received 2–8 mg doses. Twelve patients elected to continue immunization every 3 months for up to 39 months. SCIB1 induced dose-dependent T cell responses in 88% of patients with no serious adverse effects or dose limiting toxicities. The intensity of the T cell responses was significantly higher in patients receiving 4 mg doses without tumor when compared to those with tumor ( p < 0.01). In contrast, patients with tumor showed a significantly higher response to the 8 mg dose than the 4 mg dose ( p < 0.03) but there was no significant difference in the patients without tumor. One of 15 patients with measurable disease showed an objective tumor response and 7/15 showed stable disease. 5/20 fully-resected patients have experienced disease recurrence but all remained alive at the cut-off date with a median observation time of 37 months. A positive clinical outcome was associated with MHC-I and MHC-II expression on tumors prior to therapy ( p = 0.027). We conclude that SCIB1 is well tolerated and stimulates potent T cell responses in melanoma patients. It deserves further evaluation as a single agent adjuvant therapy or in combination with checkpoint inhibitors in advanced disease.